Curriculum Design in Higher Distance Education Focused on the Self-Determination of Motivation (Docentes 2.0 Journal, 2022)
Higher education in Mexico, since its inception, has faced enormous lags that prevent the well-being of the country's population. One of the main problems of the educational system in Mexico is that, despite the joint efforts of the state and public and private education institutions, education is not guaranteed to most citizens. The research aimed to develop a methodology for creating higher-level distance study plans. The study was based on the analytical-synthetic method, pragmatic paradigm, mixed approach, sequential exploratory design, sequential type, and longitudinal cut. The total population of students of the Faculty of Informatics of the Autonomous University of Querétaro is 840, of which 87 students from different careers were selected through a convenience sample. For the methodological design, a systematic review and a survey instrument were carried out to collect the indicators of the context variables, characteristics, and needs of the students in distance study plans. For the analysis of the results, descriptive and reliable methods were used to support the research. As a result, a methodology was proposed for curriculum design based theoretically on the qualities of distance education. In future work, the design of a web system to support curriculum design based on the proposed methodology was proposed.
Keywords: Curriculum design; discance higher education; selfdetermination of motivation